The Impact of Experiential Marketing, Destination Image, and Viral Marketing on Visitor Satisfaction in the Post-Pandemic Tourism Industry of Central Sulawesi - A, Muhammad Umar; Rahman, Abd.; Yasin, Muhammad; Marjun, Marjun; Latoki, Labandingi; Kamal, Kamal (TechTalent & Business Review, 2025)
The Covid-19 pandemic has caused a decrease in the number of visitors to tourist attractions in Central Sulawesi. The government and managers have made various innovations to increase the bargaining power of tourist destinations. In the competitive landscape of the tourism industry, these innovations are crucial for attracting visitors and maintaining a positive reputation. One of the improvements made to the facilities and maintenance equipment is to ensure that tourists feel satisfied when visiting. The manager carries out emotional experiences, destination images, and viral marketing strategies to provide a sense of satisfaction to visitors. These strategies are essential for enhancing customer engagement and loyalty, which are vital in a recovering market. This study analyses experiential marketing, destination image, and viral marketing on customer satisfaction. This research involved 100 tourist visitors in Central Sulawesi. The findings of this study indicate that simultaneously the three variables have a significant positive effect, but partially they do not. The EM and VM variables each positively affect visitor satisfaction, while the DI variable does not. This highlights the need for tourism managers to prioritize experiential and viral marketing techniques in their strategies. This research suggests to tourism managers that they continue to make efforts to improve the destination's image to increase visitor satisfaction and simultaneously increase the number of visitors and return visits of tourists. Ultimately, adopting a holistic approach that combines these elements can help strengthen the overall competitive position of Central Sulawesi's tourism industry.